Eating behavior, phytoestrogen intake and chronotype in relation with premenstrual syndrome among female college students - Rahmah, Hiya Alfi; Afiattami, Adendita Azmi; Khoiriani, Izzati Nur; Wahyurin, Izka Sofiyya (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
Background: Premenstrual syndrome (PMS) is a group of physical, behavioral, and emotional problems that occur before menstruation. Although the exact cause of this illness is unknown, various studies have suggested that it may be brought on by dietary, behavioral, or hormonal changes. Objectives: This study examined how eating behavior, phytoestrogen intake, and chronotype related to PMS in female college students at Universitas Jenderal Soedirman, Indonesia.Materials and Methods: Data were collected using a cross-sectional design with a cluster sampling method. This study was conducted with 104 participants, with the criteria: aged 18-22 years, class of 2020-2022, physically healthy, and willing to participate in the entire series of studies. The exclusion criteria in this study were taking sleeping pills, using hormonal therapy, and being diagnosed with a gynecological disorder. Statistical data analysis using the Spearman Correlation test. The Dutch Eating Behavior Questionnaire (DEBQ) was used to assess eating behavior, Semiquantitative Food Frequency Questionnaire (SFFQ) to assess phytoestrogen intake, Morningness-Eveningness Questionnaire Self Assessment Version (MEQ-SA) to assess chronotype, and Shortened Premenstrual Assessment Form (SPAF) to assess PMS.Results: Of the 104 participants, 99% reported having experienced symptoms of PMS. 90.4% of participants reported consuming phytoestrogens at a lower level than the sufficiency level. Emotional eating dominated the eating behavior characteristics with a 69.2% prevalence, while half of the respondents (59.6%) had a morning chronotype. Eating behavior, especially restrained eating and external eating was significantly correlated with PMS severity (p<0.023; r=0.222); (p=0.002; r=0.304). Phytoestrogen intake was significantly associated with PMS (p=0.007; r=-0.264). However, emotional eating and chronotype did not correlate with PMS.Conclusion: Eating behaviors: restrained, external eating, and phytoestrogen intake were associated with PMS while emotional eating and chronotype showed no correlation with PMS severity.